Phase I And Phase Ii Drug Metabolism Study Of Mitragynine In Normal And Diabetes Induced Rat - Anwar, Rukhsana (2013)
Mitragynine is a major indole alkaloid abundantly isolated from M. speciosa leaves. Mitragynine exhibits psychoactive properties and shows morphine-like depressant effect and cocaine-like stimulant effects. Mitragynine also shows antitussive and antidepressant-like effects. The current research was undertaken to evaluate the in vitro and in vivo effect of mitragynine on phase I and phase II drug metabolizing enzymes, namely aminopyrine N-demethylase (APND), UDP-glucuronosyl transferase (UGT) and glutathione S-transferase (GST) in normal and diabetes Sprague-Dawley (SD) rat liver. The in vitro effect of mitragynine on APND activity in relation to factors of age, gender and diabetes was determined in rat hepatocytes. Moreover, the possible mechanism of induction of aminopyrine N-demethylase activity by mitragynine was also investigated in SD rat hepatocytes. In addition, western blot analysis was carried out for in vivo CYP2C12 and UGT1A6 and GSTM1 proteins expression in normal and diabetic rats. Aminopyrine, p-nitrophenol and 1-chloro-2,4-dinitro benzene were used as a probes to determine the APND, UGT and GST activity respectively. A range of mitragynine concentration (0.0025 – 250 μM) was used for all in vitro enzyme assays in tested groups of SD rats. The mitragynine 50 mg/kg of body weight was administered orally to SD rats for in vivo study. Results of in vitro study showed that mitragynine significantly (p < 0.05) enhanced APND activity in rat hepatocytes as well as significantly inhibited microsomal UGT and cytosolic GST activity in normal and diabetic